Communication efficiency as an indicator of the professionalism of the preschool nurse educator - Tasić, Radica; Jovčić, Ljiljana; Ranković, Dragica; Gašić, Tijana (Education and Research in Health Sciences, 2026)
Introduction: Communication is a complex and dynamic process through which verbal and nonverbal messages are sent and received. Communication is a skill that can be learned, practiced, and improved. Strong communication skills contribute to more effective verbal and nonverbal expression, resulting in higher-quality interpersonal understanding both in everyday life and in professional settings. Communication forms the foundation of the professional competence of a preschool nurse educator and represents a key factor in the success of educational work within preschool institutions. Its role is particularly emphasized in working with infants and toddlers, where empathy, active listening, and nonverbal cues are crucial for establishing trust and emotional security. Aim: The aim of this research was to examine the development of communication skills among preschool nurse educators and to determine the influence of sociodemographic factors on the perception and application of communication competencies in working with children and parents. Methods: The research was conducted in eight facilities of the preschool institution „Lane“ in the municipality of Grocka. The sample included 50 preschool nurse educators who voluntarily and anonymously completed a questionnaire. The data were analyzed using descriptive, analytical, and statistical methods. Results: The findings indicate a high level of awareness of the importance of communication (96% of participants), as well as a strong readiness to adapt communication to the child’s developmental level and to apply active listening techniques. Statistically significant differences were found in relation to work experience and education level. Younger educators and those with higher education demonstrated greater agreement with statements concerning the importance of verbal and nonverbal communication. Conclusion: Communication is confirmed as a complex professional skill that requires continuous improvement and adaptation to the individual characteristics of children. Formal education, professional development, and reflective practice contribute to enhancing the quality of communication in preschool settings.